Limited carbon and biodiversity co‐benefits for tropical forest mammals and birds. Issue 4 (8th June 2016) - Beaudrot, Lydia; Kroetz, Kailin; Alvarez‐Loayza, Patricia; Amaral, Ieda; Breuer, Thomas; Fletcher, Christine; Jansen, Patrick A.; Kenfack, David; Lima, Marcela Guimarães Moreira; Marshall, Andrew R.; Martin, Emanuel H.; Ndoundou‐Hockemba, Mireille; et al.
Abstract: The conservation of tropical forest carbon stocks offers the opportunity to curb climate change by reducing greenhouse gas emissions from deforestation and simultaneously conserve biodiversity. However, there has been considerable debate about the extent to which carbon stock conservation will provide benefits to biodiversity in part because whether forests that contain high carbon density in their aboveground biomass also contain high animal diversity is unknown. Here, we empirically examined medium to large bodied ground‐dwelling mammal and bird (hereafter "wildlife") diversity and carbon stock levels within the tropics using camera trap and vegetation data from a pantropical network of sites. Specifically, we tested whether tropical forests that stored more carbon contained higher wildlife species richness, taxonomic diversity, and trait diversity. We found that carbon stocks were not a significant predictor for any of these three measures of diversity, which suggests that benefits for wildlife diversity will not be maximized unless wildlife diversity is explicitly taken into account; prioritizing carbon stocks alone will not necessarily meet biodiversity conservation goals. We recommend conservation planning that considers both objectives because there is the potential for more wildlife diversity and carbon stock conservation to be achieved for the same total budget if both objectives are pursued in tandem rather than independently. Tropical forests with low elevation variability and low tree density supported significantly higher wildlife diversity. These tropical forest characteristics may provide more affordable proxies of wildlife diversity for future multi‐objective conservation planning when fine scale data on wildlife are lacking.